Integration and coherence in food governance—a comprehensive analysis of food security public programs in Chile - del Valle M, Martín; Shields, Kirsteen; Boza, Sofia (Frontiers in Sustainable Food Systems, 2024)
This study critically examines Chilean food governance. In particular it focuses on two aspects of inter-ministerial governance: policy “integration” and policy “coherence.” It does so by evaluating the alignment between two key policy objectives within the Chilean government; the Social Determinants of Health (SDH) and National Food and Nutrition Policy (NFNP) objectives. This is accomplished by using publicly available data at the Integrated Bank of Social Programs (BIPS – Banco Integrado de Programas Sociales) collected in 2021. Utilizing mixed methods including content analysis, program review, and financial analysis, 245 public programs were scrutinized. Only 0.042% of the 2021 national budget for public programs was allocated to n = 70 key programs directly addressing food and nutrition security (FNS), highlighting significant resource disparities among ministries. While some inter-ministerial integration was observed, overall coherence with NFNP objectives, particularly in “health integration and intersectorality,” was lacking. Since disparities in resource allocation and neglect of stability and agency within food security across ministries are identified, indicating a variegated approach to food security with differing emphases on availability, utilization, and access, this study calls for a collaborative, multi-sectoral strategy to bridge policy gaps and enhance coherence in addressing food security challenges. Its findings contribute to the discourse on food governance, offering insights into policy implementation gaps and suggesting avenues for enhancing inter-ministerial integration and coherence. This research underscores the importance of a comprehensive approach to policy formulation and execution in achieving NFNP goals and addressing the complex challenges of food security in Chile.